Physiological and anthropometric characteristics of young soccer players according to their playing position: Relevance for their selection process - Gil, S. M.; Gil, J.; Ruiz, F.; Irazusta, A.; Irazusta, J. (The Journal of Strength and Conditioning Research, 2007)
The aim of this study was to establish the anthropometric and physiological profiles of young nonelite soccer players according to their playing position, and to determine their relevance for the selection process. Two hundred forty-one male soccer players who were members of the Getxo Arenas Club (Bizkaia) participated in this study. Players, age 17.31 (+/- 2.64) years, range 14-21 years, were classified into the following groups: forwards (n = 56), midfielders (n = 79), defenders (n = 77), and goalkeepers (n = 29). Anthropometric variables of participants (height, weight, body mass index, 6 skinfolds, 4 diameters, and 3 perimeters) were measured. Also, their somatotype and body composition (weights and percentages of fat, bone, and muscle) were calculated. Participants performed the Astrand test to estimate their absolute and relative VO2max, an endurance test, sprint tests (30 meters flat and 30 meters with 10 cones) and 3 jump tests (squat jump, counter movement jump and drop jump). Forwards were the leanest, presenting the highest percentage of muscle. They were the best performers in all the physiological tests, including endurance, velocity, agility, and power. In contrast, goalkeepers were found to be the tallest and the heaviest players. They also had the largest fat skinfolds and the highest fat percentage, but their aerobic capacity was the lowest. In the selection process, agility and the jump tests were the most discriminating for forwards. In contrast, agility, height, and endurance were the key factors for midfielders. The defenders group was characterized by a lower quantity of fat. Thus, we may conclude that anthropometric and physiological differences exist among soccer players who play in different positions. These differences fit with their different workload in a game. Therefore, training programs should include specific sessions for each positional role.